Family dysfunction and anxious-depressive symptoms in inpatients of a substance use disorders rehabilitation center in Lima - Alarco Herrera, Rafael (2024)
Objective: To determine the relationship between family dysfunctionality and the presence of depressive/anxiety symptoms in patients hospitalized for substance use disorders. Methods: Analytical and cross-sectional study in 57 male inpatients of a substance abuse rehabilitation center in Lima. Sociodemographic and substance use information was collected; the APGAR-family, IDARE-R and IDERE-R questionnaires were applied for family dysfunctionality, anxious and depressive symptomatology, respectively. The relationship between the scores of the surveys was evaluated with the Spearman's correlation test. Results: APGAR-family scores had a non-significant inverse correlation with both the IDARE-R score (rho = -0.061; p = 0.654) and the IDERE-R score (rho = -0.084; p = 0.533). The scores obtained were 24.6 ± 7.2 for dysfunctionality, 46 ± 6.9 for depressive symptomatology, and 46.2 ± 5.4 for anxious symptomatology; it was found that 80.7% presented normal functionality, 71.9% high levels of depression, and 63.2% high levels of anxiety. The anxious symptomatology score was significantly higher in young people compared to adults; a positive correlation (Rho= 0.599, p<0.001) was found between the scores of anxious and depressive symptomatology. Conclusion: No relationship was found between anxious-depressive symptoms and the level of family dysfunctionality. A positive relationship was identified between the scores of anxious and depressive symptomatology among the members of the evaluated sample; likewise, a higher degree of anxiety among young probands was found, similar to the depression measurements but without being significant in the latter.